ASSESSMENT OF ANTIDIABETIC ACTIVITY OF THE TRADITIONAL INDIAN AYURVEDIC FORMULATION BRAHMI GRITHAM IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Sabina, Evan Prince; Baskaran, Udhaya Lavinya; Martin, Sherry Joseph; Swaminathan, Monisha; Bhattacharya, Yashodhara; Tandon, Shreni (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of the present study was to determine the antidiabetic activity of Brahmi gritham a traditional Indian ayurvedic formulation in streptozotocin-induced diabetes in rats. Methods: Diabetes was induced by a single intra-peritoneal injection of streptozotocin (55mg/kg body weight) in the experimental animals. The anti-hyperglycaemic potential of Brahmi gritham (500 mg/kg body weight) was studied by estimating the levels of plasma blood glucose and the levels of serum total cholesterol, triglycerides, total protein and albumin in the experimental rats. The serum renal functional (creatinine; urea; uric acid) and liver functional markers (aspartate transaminase; alanine transaminase; alkaline phosphatase) were also measured. The tested parameters were compared with those of the normal and the standard drug glibenclamide-treated rats. Histological analysis of the liver was done in order to visualize the efficacy of Brahmi gritham in preventing changes in liver histology in diabetic rats. Results: Brahmi gritham showed significant (p<0.05) reduction in the elevated levels of plasma glucose, serum liver and renal function markers and total cholesterol. The formulation was also effective in restoring normal total protein and albumin levels in the serum of experimental rats. Conclusion: The study revealed significant antidiabetic potential of Brahmi gritham in the experimental rats indicating its role in the effective management of diabetes.